2020
DOI: 10.1021/acs.jpcc.0c06842
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Lithium into Graphite: Insights from First-Principles Simulations

Abstract: Understanding ion intercalation at electrode–electrolyte interfaces is key to the development of energy storage and water desalination. In this work, we investigate Li+ kinetics at a prototypical interface between graphite anodes and an organic electrolyte, and we elucidate key factors that determine ion transport, using first-principles methodology coupling ab initio molecular dynamics simulations with a solvation model. We show that surface chemical composition significantly influences the kinetics of ion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Therefore, fast-charging performance can be achieved with optimization of the overall cell design and components including active and non-active materials, electrode architecture, separator and electrolyte. [2][3][4][5][6][7][8] At the electrode level, reduced mass loading generally improves the rate performance at the expense of energy density. Hence, electrode properties (such as loading, porosity, density, electric conductivity and tortuosity) need to be tailored carefully to meet both requirements of fast kinetics and high energy density.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, fast-charging performance can be achieved with optimization of the overall cell design and components including active and non-active materials, electrode architecture, separator and electrolyte. [2][3][4][5][6][7][8] At the electrode level, reduced mass loading generally improves the rate performance at the expense of energy density. Hence, electrode properties (such as loading, porosity, density, electric conductivity and tortuosity) need to be tailored carefully to meet both requirements of fast kinetics and high energy density.…”
Section: Introductionmentioning
confidence: 99%
“…[5] At the interface between the liquid electrolyte and the graphite, the charging process comprises of very complex intermediate steps (desolvation of the lithium ions, their migration through the solid electrolyte interface -SEI, access to the edge-planes of the graphite structure, and finally intercalation between the graphene layers into the graphite bulk), each with specific reaction kinetics. [6,7] Indeed, many studies have suggested that the lithium intercalation process and its related kinetics are the main factors determining the fast-charging ability of the whole battery system. [8][9][10] Even though the mechanism of interface reactions and the rate-determining step of the lithium intercalation reaction remain partly unclear due to their complexity, the importance of the carbon surface is well established.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations